The Role of Transformational Leadership in Improving Employee Performance and Academic: A Literature Review - Dewi Putriani; Oscar Jayanagara (Jurnal Administrasi Publik, 2026)
Transformational leadership is recognized as a leadership style capable of enhancing human resource motivation, engagement, and performance. Numerous studies have shown that this approach positively impacts organizational effectiveness across various sectors. This study aims to systematically review the influence of transformational leadership on performance, both in the general workforce context and in academic settings. This study employed a systematic literature review based on PRISMA guidelines. A total of 27 empirical articles published between 2005 and 2025 were analyzed to identify patterns of findings, mediating variables, and contextual factors influencing the relationships. The review indicates that transformational leadership consistently improves performance by increasing motivation, job satisfaction, relational trust, and work engagement. In the general organizational context, this leadership style strengthens employee commitment, productivity, and career development. Transformational leadership is an effective and adaptive approach to improving organizational and academic performance, while also fostering innovation and sustainability.